2021
DOI: 10.1007/s13555-021-00648-z
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of the Alopecia Areata Patient Priority Outcomes (AAPPO) Questionnaire in Adults and Adolescents with Alopecia Areata

Abstract: Introduction: Individuals with alopecia areata (AA) may experience significant impacts on their health-related quality of life. The novel Alopecia Areata Patient Priority Outcomes (AAPPO) questionnaire has been developed to assess hair loss signs, emotional symptoms, and activity limitations associated with AA. The objective of this study was to evaluate psychometric properties and establish scoring of the AAPPO in adults and adolescents with AA. Methods: Scoring and measurement properties of the AAPPO were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The AAPPO is a psychometrically validated AA-specific assessment of HL severity, symptoms, and impact on patients with AA [ 17 , 18 ]. This study only reports on the AAPPO ES subscale that measures AA-related emotional symptoms because detailed data on HL were collected in the PRF and the PSC questionnaires, while activity impairment was covered in the WPAI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAPPO is a psychometrically validated AA-specific assessment of HL severity, symptoms, and impact on patients with AA [ 17 , 18 ]. This study only reports on the AAPPO ES subscale that measures AA-related emotional symptoms because detailed data on HL were collected in the PRF and the PSC questionnaires, while activity impairment was covered in the WPAI.…”
Section: Methodsmentioning
confidence: 99%
“…However, this online patient-reported study neither used any validated instruments for work productivity loss (WPL) or activity impairment nor fully characterized the patients’ AA history [ 14 ], which may undermine the true impact of AA extent, especially AA-related ES, on work productivity. Hence, in this real-world data study, we sought to examine the extent of AA-related ES burden on work productivity and activity impairment among patients with AA using two validated instruments—the Work Productivity and Activity Impairment (WPAI) and the AA Patient Priority Outcomes emotional symptoms (AAPPO ES) subscale [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The case study comprised two male patients 26 . Only three studies reported mean age, 12.1, 14 and 15 years 21,27,28 . The case study described the patient's extent of AA clinically; one study rated AA severity as mild, moderate or severe 22,26 .…”
Section: Resultsmentioning
confidence: 99%
“…The case study described the patient's extent of AA clinically; one study rated AA severity as mild, moderate or severe 22,26 . The Alopecia Areata Patient Priority Outcomes (AAPPO) development and validation studies reported severity as ordinal Severity of Alopecia Tool (SALT) score categories 27,28 . Two studies measured the SALT Scores 29 but did not report them separately for the paediatric subgroup 24,25 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The Brandwatch artificial intelligence-powered database identified posts related to AA treatments. Natural language processing provided a Patient Global Impression of Change (PGIC) score 4 following treatment for each post. Emolex identified underlying positive or negative emotion behind posts.…”
mentioning
confidence: 99%